(untitled) (Journal of Philosophy Culture and Political Science, 2025)
The relevance of the topic under consideration is determined by the need to consolidate civil society, harmonize interethnic relations and support cultural diversity in the context of global transformations and internal social changes. The APK is seen as an important socio-political mechanism that contributes to the integration of ethnic communities and the formation of a common Kazakh identity on a civilian basis. The main purpose of the study is to determine the role in the APK in preserving national identity, as well as to analyze its contribution to the development of a single cultural and historical space, considering international practices, including Turkish experience. The methodological basis of the study is the principles of a systemic and institutional approach. The methods used include comparative analysis, questionnaires, quantitative and qualitative analysis of empirical data, as well as interpretation of legal and strategic documents regulating the activities of the Assembly of the People of Kazakhstan and similar foreign institutions. The work includes a comparative analysis with Turkey, where mechanisms for preserving national identity through similar social institutions are studied. The legal, cultural and institutional aspects of the work of the APK and Turkish organisations aimed at consolidating society are considered. Particular attention is paid to public perception of the APK’s activities, analysed on the basis of a fundamental sociological survey - a study to identify citizens’ assessment of the effectiveness of the APK’s work, its contribution to the harmonisation of interethnic relations and the preservation of ethnocultural diversity. The article outlines the main areas of activity of the APK and its prospects for development in the further preservation of national unity. The results of the survey make it possible to assess the level of public trust in the APK and to identify possible areas of work for the Assembly of the Peoples of Kazakhstan. Based on the analysis, it can be concluded that the majority of respondents perceive the APK as an effective tool for strengthening interethnic harmony and the formation of national identity. The practical significance of the work lies in the fact that its results can be applied in the development of state policy in the national sphere and the improvement of institutions of public dialogue in a multi-ethnic community. The novelty and relevance of the study lies in a comparative analysis of the practices of similar institutions in Turkey, as well as in relying on empirical sociological data reflecting the population’s perception of the activities of the Assembly of the People of Kazakhstan. The results provide an opportunity to assess the degree of public support for the ANC and reveal the scale of its influence in modern cultural and social transformations. Keywords: Assembly of the People of Kazakhstan, social culture institute, Turkey, national identity, cultural identity, interethnic agreement, cultural diversity, civil unity. Abbreviations: APK, CIS, RK.